Properties of Fuzzy Implications obtained via the Interval Constructor - Bedregal, B.R.C.; Santiago, R.H.; Reiser, R.H.S.; Dimuro, G.P. (Trends in Computational and Applied Mathematics, 2007)
This work considers an interval extension of fuzzy implication based on the best interval representation of continuous t-norms. Some related properties can be naturally extended and that extension preserves the behaviors of the implications in the interval endpoints.